WS2 Nanoflowers as Efficient Electrode Materials for Supercapacitors. Issue 3 (16th December 2021) - Mohan, Visakh V.; Manuraj, Mohan; Anjana, Padmaja M.; Rakhi, Raghavan B.
Abstract : Supercapacitors are considered as the next‐generation energy storage devices due to their unique performance features. Properties such as large surface areas, high theoretical capacitance, and occurrence of efficient redox reactions at their surfaces make 2D WS2 transition metal dichalcogenides propitious constituents in energy storage devices. Herein, the synthesis of WS2 nanoflowers by a facile hydrothermal technique is reported. Free‐standing flexible supecapacitor electrodes are fabricated by the deposition of the WS2 nanoflowers over flexible conducting carbon fabric substrate. The electrochemical performance of the as‐prepared material is evaluated in a symmetric two‐electrode configuration. The WS2 symmetric capacitor delivers a significant specific capacitance of 119 F g −1 at 1 A g −1 current density. The device exhibits outstanding stability and nearly 100% capacitance retention after 10 000 charge–discharge cycles. Abstract : A symmetric supercapacitor based on WS2 nanoflowers is developed. The supercapacitor offers a specific capacitance of 119 F g −1 at 1 A g −1 and exhibits outstanding cycling stability with nearly 100% capacitance retention after 10 000 charge–discharge cycles.